Dural Defect Repair in Translabyrinthine Acoustic Neuroma Surgery and Its Implications in Cerebrospinal Fluid Leak Occurrence - Netto, Aloysio Augusto Tahan de Campos; Colafêmina, José Fernando; Centeno, Ricardo Silva (Journal of Neurological Surgery Part B: Skull Base, 2012)
Cerebrospinal fluid (CSF) leak is a complication that may occur after translabyrinthine (translab) acoustic neuroma (AN) removal. The aim of this study is to verify the incidence of CSF leak using two techniques for dural defect closure in translab AN surgery and present a new technique for dural repair. A retrospective study was held, reviewing charts of 34 patients in a tertiary neurotologic referral center. Out of these 34 patients that underwent translab AN excision in a 1-year period, 18 had their dural defect repaired using only abdominal fat graft and 16 using synthetic dura substitute (SDS) plus abdominal fat tissue. One patient (5.5%) in the first group had CSF leak and 1 (6.2%) in the second group had CSF leak postoperatively. Our data suggest that there are no significant differences in CSF leak rates using both techniques, although studies in a larger series must be undertaken to conclude it. We believe that the development of some points in the new technique for dural repair can achieve better results and reduce the CSF leak incidence in the translabyrinthine acoustic neuroma surgery in the near future.
Keywords: acoustic neuroma; translabyrinthine; cerebrospinal fluid leak; dural defect